دراسة نظرية العقل واللغة الشفة لدى الأفراد المصابين بمرض الزهايمر- المرحلة الأولى و الثانية- - محمد بوشناق سعدية (البليدة2- كلية العلوم الإنسانية و الإجتماعية, 2025)
تهدف الدراسة الحالية الى البحث في التفاعل بين الأداء المعرفي والعاطفي في نظرية العقل ومشاركتهما في اللغة الشفهية في المرحلة الأولى والمتوسطة من الزهايمر، باتباع المنهج الوصفي وتحديدا أسلوب دراسة حالة عبر تطبيق بطاريتي "OLTA" لتقييم اللغة الشفهية بمستوياتها في الفهم والإنتاج وبطارية "TOMA" لتقييم مهام نظرية العقل المعرفية والعاطفية المصممة من طرفنا والموجهة لفئة الراشدين. على مجموعة - من مرضى الزهايمر في المرحلة الأولى والمتوسطة بعين النعجة ولاية الجزائر. لنتوصل أخيرا الى: يشارك الجانب العاطفي لنظرية العقل على اللغة الشفهية من خلال دعم فهم واسناد الحالة العقلية الشعورية لتبرير سلوكات الآخرين، وبالتالي الأثر البراغماتي للغة في المرحلة الأولى للزهايمر. - يشارك الجانب المعرفي لنظرية العقل في اللغة الشفهية خلال المرحلة الأولى للزهايمر في القدرة على التصحيح المعجمي لدلالة المفردات وأن التمييز بين (الذات (الآخر) يدعم توظيف الضمائر الشخصية واستنتاج المعنى الضمني للعبارات اللغوية. يؤدي الانخفاض في فهم التعبيرات العاطفية للآخرين في المواقف غير المباشرة خلال المرحلة المتوسطة للزهايمر الى ضعف قدرة المريض على فهم الجمل اللغوية استنادا للسياق العام في ظل موقف تفاعلي. يؤثر ضعف القدرة على تثبيط المنظور الظاهري وتبني المنظور الحقيقي الى انخفاض القدرة على تثبيط المعنى الحرفي للعبارة اللغوية وتوجيه التفكير للمعنى الضمني، وبالتالي ضعف المستوى The present study aims to investigate the interaction between the cognitive and affective components of theory of mind and their involvement in oral language in patient's early and middle stages of Alzheimer's. Adopting a descriptive case study approach, the research utilizes the <<OLTA» battery to assess oral language- specifically comprehension and production- and the << TOMA» battery, designed by the researcher, to evaluate both cognitive and affective theory of mind tasks in adults. The study was conducted on a sample of Alzheimer's patients in the early and middle stages in Ain Naadja, Algeria. The findings revealed the following: - The affective components of theory of mind is involved in oral language by facilitating the understanding and attributing of emotional mental states, which support the interpretation and justification of others' behaviors. This, in turn enhances the pragmatic use of language in the early stage of Alzheimer's disease. The cognitive component of theory of mind contributes to oral language in the early stage of Alzheimer's by enabling lexical-semantic correction and supporting the differentiation between self and others, thereby improving the use of personal pronouns and the inference of implicit meanings in linguistic. In the middle stage of Alzheimer's, reduced ability to understand others' emotional expressions in indirect contexts leads to impaired comprehension of linguistic sentences based on general contextual cues in interactive situations. A diminished capacity to inhibit the apparent perspective and adopt a deeper, more accurate one results in reduced ability to
Keywords: اللغة الشفهية; نظرية العقل; مرض الزهايمر